2004
DOI: 10.1007/s10832-004-5156-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Acceptor Doped BaTiO3

Abstract: Electrical properties of acceptor (Mn, Mg or Mn + Mg)-doped BaTiO 3 ceramic have been studied in terms of oxygen vacancy concentration, various doping levels and electrical degradation behaviors. The solubility limit of Mn on Ti sites was confirmed to be close to or less than 1.0 mol%. Oxygen vacancy concentration of Ba(Ti 0.995−x Mg 0.005 Mn x )O 2.995−y (x = 0, 0.005, 0.01) was estimated to be ∼50 times greater than that of the un-doped BaTiO 3 . The leakage current of 0.5 mol% Mn-doped BaTiO 3 was stable wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…O ) and behave as an acceptor impurity [2][3][4][5][6][7][8][9][10]. The increase in oxygen vacancy concentration by acceptor doping (Mn 3+ , Mg 2+ ) suppresses BaTiO 3 to be reduced as MLCC materials with Ni-electrodes.…”
Section: Number Of Oxygen Vacancy (V ··mentioning
confidence: 99%
See 2 more Smart Citations
“…O ) and behave as an acceptor impurity [2][3][4][5][6][7][8][9][10]. The increase in oxygen vacancy concentration by acceptor doping (Mn 3+ , Mg 2+ ) suppresses BaTiO 3 to be reduced as MLCC materials with Ni-electrodes.…”
Section: Number Of Oxygen Vacancy (V ··mentioning
confidence: 99%
“…The increase in oxygen vacancy concentration by acceptor doping (Mn 3+ , Mg 2+ ) suppresses BaTiO 3 to be reduced as MLCC materials with Ni-electrodes. However, the oxygen vacancy is the most mobile ionic species in BaTiO 3 lattices and the electro-migration of charged oxygen vacancies in dc fields is accountable for the electrical degradation of BaTiO 3 -based ceramic capacitors [2,6,7,[11][12][13][14].…”
Section: Number Of Oxygen Vacancy (V ··mentioning
confidence: 99%
See 1 more Smart Citation
“…Yuan et al reported that the coreshell structure was formed for Nb-doped BaTiO 3 resulted from a low diffusivity of Nb 5þ ions into BaTiO 3 when grain growth was inhibited and Nb 5þ reported as donor ion and reduce the leakage current. 20,21 Parjansri et al 22 synthesized the Nb 5þ doped Ba 0:90Ca0:10 Zr 0:10 Ti 0:90 O 3 ceramics by using solid-state reaction method and reported that the average grain size values vary in the range 12:62-1:86 m. In their paper they reported that Nb doping lead to decrease the ferroelectric, piezoelectric, and electromechanical properties. The Mn 4þ ion changes the electrical and dielectric properties of barium titanate ceramics and also has a beneficial effect on the reduction of dissipation factor.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese, as an acceptor dopant, is usually used to improve the properties of the BaTiO 3 -based ceramics. Microstructure and electrical properties of Mn-doped BaTiO 3 have been extensively studied by numerous researchers [3][4][5][6][7][8][9][10][11][12][13][14][15]. For the donor-doped positive temperature coefficient of resistance (PTCR) ceramics, manganese depresses the grain size and enhances the electrical resistivity near the Curie temperature of BaTiO 3 [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%